Local Neighbors as Positives, Regional Neighbors as Negatives: Competing Channels in the Relationship between Others' Income, Health, and Happiness - John Ifcher; Homa Zarghamee; Carol Lee Graham (Institute for the Study of Labor (IZA), 2016)
We develop a theoretical framework that integrates four distinct channels through which others' income can affect utility: public goods, cost of living, expectations of future income, and direct effects (relative income hypothesis and/or altruism). We empirically estimate the relationship with U.S. well-being and health data from Gallup and geographically-based median-income data for ZIP codes and MSAs. The relationship is proximity-dependent: positive (negative) with ZIP-code (MSA) median income as reference income, suggesting that positive (negative) channels dominate locally (regionally) and reconciling seemingly divergent results from the literature. Additional analyses provide evidence of the importance of the public-goods and cost-of-living channels.
Keywords: D6; D31; I31; 330; relative utility; reference group; others' income; relative income hypothesis; subjective well-being; income comparison; happiness